2021
DOI: 10.2147/jbm.s286743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gasoline Exposure on Hematological Parameters of Gas Station Workers in Mekelle City, Tigray Region, Northern Ethiopia

Abstract: Background:The adverse health effects of chronic gasoline exposure may be related to impairment of the hematopoietic system with bone marrow suppression, an increased risk of blood cell morphology abnormality and developing cancer. Objective: To assess the effect of gasoline exposure on hematological parameters among gas station workers in Mekelle City, Tigray Region, Northern Ethiopia. Methods: This cross-sectional study was carried out on 43 subjects (exposed group) and 77 subjects (unexposed group) with mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
6
1
2
Order By: Relevance
“…The present study also indicated a significant reduction in RBCs count, Hb content, HCT%, MCV, and MCH in gasoline-exposed rats compared to the control. These results agreed with the data of Teklu et al 44 , who attributed this to the cytotoxic effects of the benzene constituent of gasoline, which depresses hematopoiesis in bone marrow, causing aplastic anemia. Moreover, naphthalene, as one of the gasoline constituents, is also known to affect the red cell membranes, leading to hemoglobin denaturation and hemolytic anemia 45 .…”
Section: Discussionsupporting
confidence: 92%
“…The present study also indicated a significant reduction in RBCs count, Hb content, HCT%, MCV, and MCH in gasoline-exposed rats compared to the control. These results agreed with the data of Teklu et al 44 , who attributed this to the cytotoxic effects of the benzene constituent of gasoline, which depresses hematopoiesis in bone marrow, causing aplastic anemia. Moreover, naphthalene, as one of the gasoline constituents, is also known to affect the red cell membranes, leading to hemoglobin denaturation and hemolytic anemia 45 .…”
Section: Discussionsupporting
confidence: 92%
“…All these investigations declared that exposure to different chemicals including benzene at working place has an adverse effect on the cholesterol level. Since cholesterol is one of the important predictors of cardiovascular diseases, these workers are at risk of developing cardiovascular diseases [12]. For blood creatinine level, our result showed that exposed workers had no evident effect on blood creatinine level (p>0.05), according to the investigation of the methodology used in this study (Table 4).…”
Section: Resultsmentioning
confidence: 57%
“…Ayrıca ortalama hücre hemoglobini ve ortalama hücre hemoglobin konsantrasyonu, maruz kalan katılımcılarda kontrol grubu ile karşılaştırıldığında, önemli ölçüde daha yüksek olarak belirtilmiştir. Ek olarak bu çalışmada hematokrit seviyeleri, kırmızı kan hücresi sayısı, hemoglobin konsantrasyonu, trombosit sayısı, platelet hacmi, lenfosit yüzdesi ve nötrofil yüzdesi gibi hematolojik parametrelerin, maruz kalma süresi arttıkça azaldığı bildirilmiştir [28]. Diğer bir çalışmada akaryakıt istasyonu çalışanlarının benzen, ksilen, etilbenzen ve toluen gibi genotoksik kimyasallara maruziyet sonucunda meydana gelen genotoksisite profilleri incelenmiştir.…”
Section: Benzin İstasyonu çAlışanlarında Olası Advers Sağlık Etkileriunclassified